POLA ASUH ANAK DALAM MENINGKATKAN PRESTASI BELAJAR DI PANTI ASUHAN AISYIYAH PAYAKUMBUH - Cici Marshela; Linda Yarni (Pusat Riset dan Inovasi Nasional, 2023)
Children are the seeds of the nation and state that will continue the struggle and ideals of the nation. Therefore, children need guidance and direction from an early age from their parents to face the various struggles they will achieve. While the family is the smallest group unit that is first encountered by children and it is from the family that children get non-formal education for the first time. Therefore, parenting is very important in educating children for their success in the future. Services and fulfillment carried out for children in orphanages are useful so that children can learn to be independent and not depend on others after leaving the orphanage. The education and skills obtained at the Aisyiyah Payakumbuh Orphanage have a strong personal attitude, are optimistic about themselves, and can open themselves up to always be enthusiastic about living the wheel of life. This type of research is descriptive qualitative, using data collection methods, namely observation and interviews. The purpose of this study is to find out how the parenting style of children at the Aisyiyah Payakumbuh Orphanage, the supporting factors and inhibiting factors in improving children's learning achievement at the Aisyiyah Payakumbuh Orphanage. Based on research conducted by researchers, the parenting style that is applied to children at the Aisyiyah Orphanage is democratic parenting, namely by giving affection, providing guidance, looking after, and also providing education and good parenting to children. In addition there are several factors inhibiting children's learning in improving learning achievement, namely limited funds or economy, then the supporting factors are the environment.